Comparison of the antiviral activity of flavonoids against murine norovirus and feline calicivirus. (February 2016) - Seo, Dong Joo; Jeon, Su Been; Oh, Hyejin; Lee, Bog-Hieu; Lee, Sook-Young; Oh, Seung Hyun; Jung, Ji Youn; Choi, Changsun
Abstract: Antiviral effect of 10 flavonoids against feline calicivirus (FCV) and murine norovirus (MNV) was investigated on Crandell-Reese feline kidney (CRFK) cells and RAW 264.7 cells. Each cells infected with FCV or MNV was treated with different flavonoids at concentrations between 50 and 300 μM. A 200 μM dose of kaempferol and daidzein significantly reduced the FCV titer by 69.76 ± 8.71 and 63.47 ± 9.82%, respectively. A 300 μM dose of quercetin and fisetin reduced the titer of FCV titer by 56.70 ± 11.39 and 41.84 ± 11.35%, respectively. The titer of MNV was reduced by 50.47 ± 6.91 and 51.21 ± 13.38% by a 50 μM dose of fisetin or a 150 μM dose of epicatechin gallate, respectively. A 50 μM dose of daidzein and 100 μM of quercetin reduced the MNV titer by 46.32 ± 8.70 and 45.78 ± 9.81%, respectively. The pre-treatment of quercetin, fisetin, daidzein, and epicatechin gallate demonstrated the anti-noroviral activity against MNV and FCV. Highlights: Pre-treatment of flavonoids significantly reduced norovirus surrogates. Co- and post-treatment of flavonoids had no effect to reduce norovirus surrogates. Quercetin, fisetin, epicatechin 3-gallate, and daizein showed the significant reduction of MNV. Kaempferol, quercetin, fisetin, and daidzein showed the significant reduction of FCV.